How to dissociate porcine ovaries: towards efficient retrieval of putative female germline stem cells - Rita L. Sousa; Sandra Farré; Martin Waterfall; Yvonne L. Odey; Kay Samuel; Evelyn E. Telfer; Peter E.J. Bols; Ruth Appeltant (Theriogenology, 2026)

Determination and quantification of microbial communities and antimicrobial resistance on food through host DNA-depleted metagenomics - Samuel J. Bloomfield; Aldert L. Zomer; Justin O'Grady; Gemma L. Kay; John Wain; Nicol Janecko; Raphaëlle Palau; Alison E. Mather (Food Microbiology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Discovery of structural deletions in breast cancer predisposition genes using whole genome sequencing data from > 2000 women of African-ancestry - Zhishan Chen; Xingyi Guo; Jirong Long; Jie Ping; Bingshan Li; Mary Kay Fadden; Thomas U. Ahearn; Daniel O. Stram; Xiao-Ou Shu; Guochong Jia; Jonine Figueroa; Robertson Adjei; et al. (Human Genetics, 2021)

Simple inheritance, complex regulation: Supergene‐mediated fire ant queen polymorphism - Samuel V. Arsenault; Joanie T. King; Sasha Kay; Kip D. Lacy; Kenneth G. Ross; Brendan G. Hunt (Molecular Ecology, 2020)
The fire ant Solenopsis invicta exists in two alternate social forms: monogyne nests contain a single reproductive queen and polygyne nests contain multiple reproductive queens. This colony‐level social polymorphism corresponds with individual differences in queen physiology, queen dispersal patterns and worker discrimination behaviours, all evidently regulated by an inversion‐based supergene that spans more than 13 Mb of a “social chromosome,” contains over 400 protein‐coding genes and rarely undergoes recombination. The specific mechanisms by which this supergene influences expression of the many distinctive features that characterize the alternate forms remain almost wholly unknown. To advance our understanding of these mechanisms, we explore the effects of social chromosome genotype and natal colony social form on gene expression in queens sampled as they embarked on nuptial flights, using RNA‐sequencing of brains and ovaries. We observe a large effect of natal social form, that is, of the social/developmental environment, on gene expression profiles, with similarly substantial effects of genotype, including: (a) supergene‐associated gene upregulation, (b) allele‐specific expression and (c) pronounced extra‐supergene trans ‐regulatory effects. These findings, along with observed spatial variation in differential and allele‐specific expression within the supergene region, highlight the complex gene regulatory landscape that emerged following divergence of the inversion‐mediated Sb haplotype from its homologue, which presumably largely retained the ancestral gene order. The distinctive supergene‐associated gene expression trajectories we document at the onset of a queen’s reproductive life expand the known record of relevant molecular correlates of a complex social polymorphism and point to putative genetic factors underpinning the alternate social syndromes.

Inferring infection hazard in wildlife populations by linking data across individual and population scales - Kim M. Pepin; Shannon L. Kay; Ben D. Golas; Susan S. Shriner; Amy T. Gilbert; Ryan S. Miller; Andrea L. Graham; Steven Riley; Paul C. Cross; Michael D. Samuel; Mevin B. Hooten; Jennifer A. Hoeting; et al. (Ecology Letters, 2017)
Our ability to infer unobservable disease‐dynamic processes such as force of infection (infection hazard for susceptible hosts) has transformed our understanding of disease transmission mechanisms and capacity to predict disease dynamics. Conventional methods for inferring FOI estimate a time‐averaged value and are based on population‐level processes. Because many pathogens exhibit epidemic cycling and FOI is the result of processes acting across the scales of individuals and populations, a flexible framework that extends to epidemic dynamics and links within‐host processes to FOI is needed. Specifically, within‐host antibody kinetics in wildlife hosts can be short‐lived and produce patterns that are repeatable across individuals, suggesting individual‐level antibody concentrations could be used to infer time since infection and hence FOI . Using simulations and case studies (influenza A in lesser snow geese and Yersinia pestis in coyotes), we argue that with careful experimental and surveillance design, the population‐level FOI signal can be recovered from individual‐level antibody kinetics, despite substantial individual‐level variation. In addition to improving inference, the cross‐scale quantitative antibody approach we describe can reveal insights into drivers of individual‐based variation in disease response, and the role of poorly understood processes such as secondary infections, in population‐level dynamics of disease.

Effects of mu opioid receptor antagonism on cognition in obese binge-eating individuals - Samuel R. Chamberlain; Karin Mogg; Brendan P. Bradley; Annelize Koch; Chris M. Dodds; Wenli X. Tao; Kay Maltby; Bhopinder Sarai; Antonella Napolitano; Duncan B. Richards; Edward T. Bullmore; Pradeep J. Nathan (Psychopharmacology, 2012)

The effects of modulating eNOS activity and coupling in ischemia/reperfusion (I/R) - Kerry-Anne A. Perkins; Sailesh Pershad; Qian Chen; Sloane McGraw; Jovan S. Adams; Christopher Zambrano; Samuel Krass; Jeffrey Emrich; Brandon Bell; Michael Iyamu; Catherine Prince; Helen Kay; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Mechanisms related to the cardioprotective effects of protein kinase C epsilon (PKC ɛ) peptide activator or inhibitor in rat ischemia/reperfusion injury - Jane Chun-wen Teng; Helen Kay; Qian Chen; Jovan S. Adams; Christopher Grilli; Giuseppe Guglielmello; Christopher Zambrano; Samuel Krass; Adrian Bell; Lindon H. Young (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)